Penerapan Dadu Pintar Dalam Meningkatkan Minat Belajar Matematika Dan Sains Pada Anak Usia Dini (Studi Kasus Paud Ar-Rohmah) - Intan Permata Sari; Putri Maslia Ali; Suci Amanah; Riski Adelina Matondang; Selvi Septiani (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to describe and analyze the application of smart dice media in increasing interest in learning mathematics and science in early childhood. This study uses a field research method with a qualitative descriptive approach supported by simple quantitative data. The subjects of the study were 20 children aged 5–6 years at PAUD Ar-Rohmah. Data collection techniques were carried out through observation, interviews, and documentation during the learning process. The media used were smart dice combined with tree-shaped props and pictures of fruits, such as apples and bananas, to help children understand the concept of simple addition and recognize tastes as part of science learning. The results of the study showed that the use of smart dice media was able to increase children's interest in learning, which was indicated by increased activity, participation, self-confidence, and enthusiasm in participating in learning. In addition, children's abilities in understanding the concept of simple addition and recognizing the taste of fruit also increased. However, there were still some children who needed guidance in understanding the learning material.